2022
DOI: 10.17503/agrivita.v41i0.3731
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Virus Symptoms in Chili Plants (Capsicum frutescens) Based on RGB Image Analysis

Abstract: Virus infection in chili plants may cause various symptoms. The complexity of the symptoms and human vision ability often become limiting factors during disease investigations. Digital image analysis is expected to become a method to assist in comprehensively describing the symptoms of plant viruses. A disease survey was conducted on cayenne pepper fields in Southeast Sulawesi Province to observe symptoms of virus infection virtually and to record the symptomatic plant using an RGB camera. The split-channel me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Fatigue when making observations, subjectivity in assessment [6], and expression of disease symptoms that are sometimes not visible due to environmental factors [7]. The complexity of symptoms due to interactions between viruses [5,8], the presence of DNA satellites that can affect the expression of symptoms [9], and the degree of plant resistance are some of the limiting factors in the application of visual observation-based assessment methods to the human eye.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue when making observations, subjectivity in assessment [6], and expression of disease symptoms that are sometimes not visible due to environmental factors [7]. The complexity of symptoms due to interactions between viruses [5,8], the presence of DNA satellites that can affect the expression of symptoms [9], and the degree of plant resistance are some of the limiting factors in the application of visual observation-based assessment methods to the human eye.…”
Section: Introductionmentioning
confidence: 99%
“…This bias is mainly caused by the subjectivity factor and variations in the evaluator's skill level, which often occur during visual observations. A previous study has reported that digital image processing can assess the severity of viral symptoms in the field (Hasan et al, 2022) and in experimental gardens (Hasan et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%